Molecular Docking Approaches in the Discovery and Development of Natural-based Functional Foods: An Opinion Study - PERMATASARI, Happy Kurnia; TASLIM, Nurpudji Astuti; AL MAHIRA, Msy Firyal Nadya; AMALIA, Nurlinah; FARRADISYA, Salsabila; PUTRI, Ritma Ratri Ayunda; ARNAMALIA, Astri; FARADIS, Muhammad Agil Wijaya; YUSUF, Muhammad; GUNAWAN, William Ben; SURYA, Reggie; MAYULU, Nelly; et al. (Nutrición Clínica y Dietética Hospitalaria, 2024)
Backgrounds and Aims: Functional foods or nutraceuticals are innovative foods that contain substances that may improve health or prevent disease, as long as the concentration is safe and high enough to provide the desired benefit. Nutrients, dietary fiber, phytochemicals, other compounds, and probiotics are a few examples of added functional ingredients. Food can be deemed "functional" if it positively impacts specific bodily processes that go beyond nutritional effects to promote health and well-being and/or prevent the development of chronic diseases. Therefore, this paper aims to elaborate opinions based on the latest evidence to introduce the molecular docking simulation approach in the discovery and development of functional foods. Results and Conclusions: In functional food research, the computer-based approach allows for the virtual screening of bioactive compounds in foods. Instead of performing extensive laboratory experiments, researchers can simulate the interactions between bioactive compounds and molecular targets using molecular docking simulations. This virtual screening process helps identify bioactive compounds in foods that have the potential to interact with specific targets, providing insights into their mechanisms of action and potential health benefits. Now the technology field continues to receive significant attention from several researchers so technological progress never goes out. This technological advancement can be integrated between functional food and digital platforms. This platform may contain personalized recommendations, track health parameters, and empower individuals to make informed choices and monitor progress.